The Influence Of Instructional Leadership On Teacher’s Performance - Mangando, Widyaskara; Riswan, Muh.; Sari, Helena Purnama; Akbar, Sahrul (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
This study aims to analyze the effect of instructional leadership on teacher performance in public high schools in North Toraja Regency. The research employs a quantitative approach with a simple correlation method. The sample consists of 136 teachers from four schools selected using simple random sampling. Data were collected through questionnaires and analyzed using simple regression. The findings reveal that instructional leadership has a positive and significant impact on teacher performance, contributing 52.7% of the variance. Regression analysis indicates that every one-point increase in instructional leadership improves teacher performance by 0.272 points. In conclusion, enhancing the quality of instructional leadership can significantly improve teacher performance.